Benchtop 1H NMR spectroscopy as a practical tool for characterization of chemically ex-changing systems in Ascorbic acid - Sevil Cikrikci (Journal of Advanced Research in Natural and Applied Sciences)
Nuclear magnetic resonance (NMR) spectra and its action on characterization of pH dependent systems are among the most useful tools in spectroscopic techniques. Nevertheless, practical considerations often limit the application of High field NMR owing to its huge dimensions, expense and time-consuming property. On the other hand, benchtop devices could be another option with portable function and permanent magnet mechanism (1–2 T) but with several disadvantages such as reduced sensitivity and low resolution. In this study, proton exchange rates depending on pH of a selected molecule, were monitored by both 800 MHz High-Field and 60 MHz Bench-top H1 NMR to be compared. L-Ascorbic acid (AA) which is an important substrate for body and biological reac-tions was chosen as a target model molecule. This study supported the use of NMR for pH dependent chemical changes due to protonation. According to spectrum results and previous literature studies, shifting behaviour of Peak 1 (assigned to C4-H13) towards lower frequencies upon pH increase, gave us its feasibility for pKa determi-nation. While High-field NMR spectroscopy demonstrated the compositional analysis of AA and proton exchanges showing couplings between protons, Benchtop NMR was displayed as a limited tool owing to broadened lines of splitting peaks. Even so, shifting tendency of Peak 1 was still obtained quantitatively and promoted the feasibility of Benchtop NMR for characterization of a model molecule which was L-ascorbic acid. In brief, this study sup-ported the effect of magnetic field strength on characterization of pH dependent chemical exchange regimes for vitamins.